SNEVhPrp19/hPso4 regulates adipogenesis of human adipose stromal cells - Khan, Abdulhameed; Dellago, Hanna; Scheideler, Marcel (Stem cell reports, 2017)
Summary Aging is accompanied by loss of subcutaneous adipose tissue. This may be due to reduced differentiation capacity or deficiency in DNA damage repair (DDR) factors. Here we investigated the role of SNEVhPrp19/hPso4, which was implicated in DDR and senescence evasion, in adipogenic differentiation of human adipose stromal cells (hASCs). We showed that SNEV is induced during adipogenesis and localized both in the nucleus and in the cytoplasm. Knockdown of SNEV perturbed adipogenic differentiation and led to accumulation of DNA damage in hASCs upon oxidative stress. In addition, we demonstrated that SNEV is required for fat deposition in Caenorhabditis elegans. Consequently, we tested other DDR factors and found that WRN is also required for adipogenesis in both models. These results demonstrate that SNEV regulates adipogenesis in hASCs and indicate that DDR capacity in general might be a pre-requisite for this process.
Available online 29 December 2016
Gesehen am 15.08.2018